TRPM2 links oxidative stress to the NLRP3 inflammasome activation - Zhong, Zhenyu (2013)
Exposure to particulate crystals can induce oxidative stress in phagocytes, which triggers NLRP3 inflammasome-mediated interleukin 1β (IL-1β) secretion to initiate undesirable inflammatory responses that are associated with both autoinflammatory and metabolic diseases. Although mitochondrial reactive oxygen species (ROS) play a central role in NLRP3 inflammasome activation, how ROS signal assembly of the NLRP3 inflammasome remains elusive. Here, we identify liposomes as novel activators of NLRP3 inflammasome and further demonstrate that liposome-induced inflammasome activation also requires mitochondrial ROS. Moreover, we found that stimulation with liposomes/crystals induced ROS-dependent calcium influx via the TRPM2 channel and that macrophages deficient in TRPM2 displayed drastically impaired NLRP3 inflammasome activation and IL-1β secretion. Consistently, Trpm2(−/−) mice were resistant to crystal-/liposome-induced IL-1β-mediated peritonitis in vivo. Together, these results identify TRPM2 as a key player that links oxidative stress to the NLRP3 inflammasome activation. Therefore, targeting TRPM2 may be effective for the treatment of NLRP3 inflamamsome-associated inflammatory disorders.